2017
DOI: 10.1016/j.psyneuen.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of testosterone in the cerebellum link to neuroticism: From adolescence to early adulthood

Abstract: Previous research has found an association between a smaller cerebellar volume and higher levels of neuroticism. The steroid hormone testosterone reduces stress responses and the susceptibility to negative mood. Together with in vitro studies showing a positive effect of testosterone on cerebellar gray matter volumes, we set out to explore the role of testosterone in the relation between cerebellar gray matter and neuroticism. Structural magnetic resonance imaging scans were acquired, and indices of neurotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 101 publications
3
23
0
Order By: Relevance
“…These data replicate the findings from our previous cross‐sectional study in adolescents (Peper, Koolschijn, et al., Schutter et al., ) and correspond with findings in other cross‐sectional samples (Op de Macks et al., ). A possible underlying mechanism could be that testosterone binds to androgen receptors in limbic brain areas, which are implicated in risky behavior (Peper & Dahl, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These data replicate the findings from our previous cross‐sectional study in adolescents (Peper, Koolschijn, et al., Schutter et al., ) and correspond with findings in other cross‐sectional samples (Op de Macks et al., ). A possible underlying mechanism could be that testosterone binds to androgen receptors in limbic brain areas, which are implicated in risky behavior (Peper & Dahl, ).…”
Section: Discussionsupporting
confidence: 90%
“…With respect to the self‐report data, we observed that higher testosterone levels in males were associated with fewer behavioral avoidance‐related characteristics, such as neuroticism and behavioral inhibition/punishment sensitivity (BIS‐scale). The potentially “suppressing” effect of testosterone on behavioral avoidance or punishment sensitivity is similar to earlier reports, including lowered fear and anxiety‐like traits during adolescence (Enter, Terburg, Harrewijn, Spinhoven, & Roelofs, ; Schutter et al., ). Interestingly, both neuroticism and behavioral inhibition/punishment sensitivity were negatively correlated with risk taking and delay discounting.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In a replication of their earlier study, Schutter et al (2017) examined the relation of depression and anxiety subscales from the NEO-PI-R Neuroticism factor in 149 healthy volunteers. To extend this research they also included a measure of Behavioural Inhibition.…”
Section: Structural Imaging Studiesmentioning
confidence: 98%